2019
DOI: 10.1029/2019gl085251
|View full text |Cite
|
Sign up to set email alerts
|

Biologically‐Relevant Trends in Springtime Temperatures Across the United States

Abstract: Long‐term trends in temperature—a primary driver of phenology—are typically evaluated using monthly or seasonal averages. However, accumulated warmth, rather than average temperature, cues phenological events; further, the amount of heat necessary to trigger activity is species‐specific. We evaluated trends in the timing of three heat accumulation thresholds encompassing spring‐season biological activity in the conterminous United States over a 70‐year period to document changes from a biologically relevant pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…Our analysis of uncertainties suggests that we can best improve & Crimmins, 2019;IPCC, 2014) would also be beneficial, as forecasts are less likely to be reliable when projected climate differs markedly from that used to estimate population responses to climatic change (Fitzpatrick & Hargrove, 2009;Saunders et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis of uncertainties suggests that we can best improve & Crimmins, 2019;IPCC, 2014) would also be beneficial, as forecasts are less likely to be reliable when projected climate differs markedly from that used to estimate population responses to climatic change (Fitzpatrick & Hargrove, 2009;Saunders et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, using newly available data from volunteer‐based networks to better understand lesser‐studied portions of the migratory cycle (e.g., relationships between local climate conditions and spatiotemporal variation in abundance of monarchs in eastern Texas) would be especially valuable and is likely to improve the accuracy of population forecasts. Instigating studies in regions where climate is highly variable and/or changing rapidly (e.g., central Michigan; Figures 2 and 3; Crimmins & Crimmins, 2019; IPCC, 2014) would also be beneficial, as forecasts are less likely to be reliable when projected climate differs markedly from that used to estimate population responses to climatic change (Fitzpatrick & Hargrove, 2009; Saunders et al, 2016). Finally, recent efforts to systematically monitor monarchs and milkweed throughout the summer breeding range, like the Integrated Monarch Monitoring Program (Cariveau et al, 2019; Weiser et al, 2019), could improve precision of population forecasts by providing high‐quality data on monarch recruitment in previously unsampled areas.…”
Section: Discussionmentioning
confidence: 99%
“…Higher variation of spring temperature before flowering than leaf‐out could partly explain the larger advance in flowering than leaf‐out for LO‐FL species, but could not account for the decreased temporal differences between leaf‐out and flowering for FL‐LO species. On the second, woody plants have been well documented to require a specific amount of heat during spring to break dormancy, and a lower heat requirement may lead to earlier development under climatic warming (Crimmins & Crimmins, 2019; Hänninen, 2016). Our results confirmed the second explanation, since we indeed found that the earlier phenological events required fewer GDD than later events for both the LO‐FL and FL‐LO species, as well as higher sensitivity to heat for flowering than leaf‐out, which suggested that in addition to S T , the sensitivity of the heat requirement could also partially account for the decreasing temporal difference between leaf‐out and flowering.…”
Section: Discussionmentioning
confidence: 99%
“…Given that climate change is likely to affect many biologically important environmental variables including both growing season length (through increases in temperature) and precipitation, we need to gain a more complete understanding of how these climatic parameters—individually and in combination—affect mean seed mass (Cayan et al, 2008 ; Crimmins & Crimmins, 2019 ; Polade et al, 2017 ). Few studies have assessed the importance of interactions between climatic parameters on seed mass (Larios et al, 2014 ; Soper Gorden et al, 2016 ), and despite the well‐documented independent effects of both precipitation and growing season length on mean seed mass (Crouch & Vander Kloet, 1980 ; de Frenne et al, 2010 ; Konarzewski et al, 2012 ; Murray et al, 2004 ), to our knowledge, no studies have investigated how these variables interact to affect population mean seed mass.…”
Section: Introductionmentioning
confidence: 99%